Dirāsa ḥawla Manshūrāt Maktabat al-Ḍāmirī li’l-Nashr wa’l-Tawzīʿ, 1425/2004 - Barāshidī, Ṣāliḥ b. Khalfān b. Muḥammad al- (Maktabat al-Ḍāmirī, 2004)
The history of Makt. al-Ḍāmirī in al-Sīb, short descriptions of a number of its publications, and a list of publications.
Keywords: Bibliographie -- Oman

Guide to Omani theses, 1970-2003 (Sultan Qaboos University, 2004)
Keywords: Bibliographie -- Oman